Emotion as one of the dominant factors of extralinguistics to succeed in language study - Seruji, Zuraini; Kamaruddin, Rohaidah; Goyi, Nalmon; Gitom, Sinit @ John (David Publishing Company, 2018)
Research on the relationship of the second language of extralinguistic factors with the achievement of Malay among multilingual Malay students in full boarding schools in Malaysia is still lacking. Recognizing this, the researchers conducted a study on the dominant extralinguistic factor in learning a second language which is emotion. Samples of respondents are from Jempol Integration Boarding School (SBPIJ), Tuanku Jaafar Science School (STJ), and Rembau Science School (SEMESRA) about 224 multilingual students. This study uses the Learning Theory presented by Rita Dunn (2004). The results show that the emotional response represented by Item D2, “I prefer to be told exactly what to do when taking note of B2” is the most dominant emotional factor for SBPIJ which is 100%. The researchers also found that D2 was also the most dominant item for SEMESRA (95%). The anxiety level of Malay students in SBPIJ is very low because reliance on the guidance of teachers is 100%. In terms of emotion, the responses of the three schools showed the same attitude. Each student is highly dependent on the direction or guidance of teachers to note B2.